The Columbellidae (Gastropoda, Buccinoidea) in the Miocene Paratethys Sea—striking diversity of a negelected group - Harzhauser, Mathias; Landau, Bernard M. (Zootaxa, 2021)
We document 37 Columbellidae species, placed in 15 genera, from the middle Miocene of the Paratethys Sea, adding about 20% of new species to the previously known Columbellidae fauna of the Paratethys. This distinct increase is based on a careful revision of museum material that was collected during the 19th century. A detailed revision revealed numerous misidentifications of published material, which greatly distorted the understanding of many species in the literature. The revised fauna reveals only minimal affinities with coeval faunas from the Proto-Mediterranean Sea and suggests a palaeogeographic subdivision within the Central Paratethys between northern and southern basins. A major drop in columbellid diversity occurred at the Langhian/Serravallian boundary, coinciding with the Miocene Climatic Transition. This event led to a severe diversity decline from a high Langhian level of 32 species, which was comparable in the number of columbellid species to that of the modern Red Sea and tropical West Africa (~23 species), down to a diversity level of nine species, equalling that of the modern Mediterranean Sea.                Auingeria nov. gen., Bellacolumbella nov. gen., Martaia nov. gen. and Defensina nov. gen. are introduced as new genera. Mitrella dacica nov. sp., Mitrella demaintenonae nov. sp., Mitrella elongatissima nov. sp., Mitrella viennensis nov. sp. and Zafrona sphaerocorrugata nov. sp. are described as new species. Costoanachis venzoi is proposed as replacement name for Anachis (Costoanachis) subcorrugata Venzo & Pelosio, 1963 non Columbella (Anachis) subcorrugata Boettger, 1906.                Lectotypes are designated for Columbella (Anachis) guembeli Hoernes & Auinger, 1880, Columbella januskiewiczi Friedberg, 1938, Columbella (Mitrella) fallax Hoernes & Auinger, 1880, Atilia (Macrurella) hilberi Cossmann, 1901, Columbella petersi Hilber, 1879, Columbella (Mitrella) complanata Sacco, 1890, Columbella (Mitrella) bittneri Hoernes & Auinger, 1880, Columbella (Orthurella) elongata var. convexula Sacco, 1890, Columbella (Anachis) moravica Hoernes & Auinger, 1880, Columbella (Mitrella) bucciniformis Hoernes & Auinger, 1880, Columbella (Anachis) haueri Hoernes & Auinger, 1880, Columbella (Anachis) austriaca Hoernes & Auinger, 1880, Pyrene (Anachis) bellardii grussbachensis Csepreghy-Meznerics, 1969, Columbella (Anachis) dujardini Hoernes & Auinger, 1880, Columbella (Anachis) zitteli Hoernes & Auinger, 1880, Columbella (Nitidella) karreri Hoernes & Auinger, 1880, and Columbella (Nitidella) katharinae Hoernes & Auinger, 1880.                Scabrellana is introduced as replacement name for the trilobite genus Scabrella Wenndorf (1990) non Scabrella Sacco, 1890.